(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Lercaritubus problematicus Flügel, Senowbari-Daryan & Di Stefano and Vangia telleri (Flügel) and enigmatic calcareous fossils, known from the Sicily, Guadalupe Mountains, USA and Oman is described from the Permian Jamal Formation of Shotori Mountains, northeast Iran. The new genus name Vangia is introduced for Uvanella? telleri Flügel. The systematic position of Vangia telleri (Flügel) nov. comb. as possibly cyanobaterium and its relationships with Bacinella irregularis Radoicic, an abundant enigmatic fossil in Jurassic-Cretaceous shallow water deposits, is discussed.